Power sector: institutional framework, issues, and new trends - Quiñones Alayza, Maria Teresa (2016)
The power sector of a country is highly relevant for its competitiveness and social development. In Peru, this sector has passed through many changes before having its current configuration, which has negative and positive aspects.In the present versus, two different perspectives come face to face as the debate about key and current topics starts. The discussion is about questions such as the “oversupply” of power generation, the creation of additional charges to the power transmission  service, or the frontiers of the regulated market.